Information experience: A domain and object of study. Issue 1 (18th October 2019) - Maybee, Clarence; Abdi, Elham Sayyad; Davis, Kate; Conrad, Lettie
ABSTRACT: Introduced into the field in 2014, "information experience" (IX) is a research domain that focuses on the ways that people derive meaning from engagement with information in the various aspects of their lives. IX is also an object of study comparable to other objects, such as information seeking or information literacy. This interactive panel will discuss aspects of IX, including the various ways it may be described in the field, and how it is manifest in a current IX research project. Two learning design models – informed learning design and information experience design (IXD) – will be introduced, exemplifying how theoretical understandings of IX can be applied in practice.